The Vordingborg project - Co-ordination of Public Transport Service - Thisgaard, Preben; Simonsen, Rikke Tovbjerg (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
This paper describes how the Municipality of Vordingborg reorganised and co-ordinated the Public Transport Service of Vordingborg. The Vordingborg Project achieved some outstanding results. Increasing the overall level of service and at the same time saving a substantial amount of money. The Vordingborg Project builds on the knowledge and development work performed by the consultancy NOVA PRO and on the EU THERMIE Project ERANTIS, and its work on a more energy and environmental efficient Public Transport. One of the main tools is a special set-up and use of standard email system and the Microsoft Excel software.